The Competitiveness of Sorghum in East Kolaka Regency - Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The purpose of this research is to assess the competitiveness of sorghum cultivation in the East Kolaka Regency. The research was carried out in Lamunde Village, Tinondo District, East Kolaka Regency, in August 2021. Sorghum farmers made up the research population, which totaled 25 persons. The research sample was chosen using the census approach, which samples the total research population. Primary and secondary data were employed as kinds and sources of information. Direct interviewing, observation, and literature review were used to gather research data. Some research factors include revenues, expenses, output, private pricing, and societal prices. The Policy Analysis Matrix technique was used to assess the competitiveness of sorghum growth. The findings revealed that sorghum farming was competitive at both the personal and social price levels, as evidenced by the value of the Private Cost Ratio of 0.16 and the value of the Domestic Resource Cost Ratio of 0.11. Because, according to research, the selling price of sorghum in the international market is much higher than the prevailing price at the farmer level, there is a need for government intervention related to increasing the selling price of sorghum at the farmer level and supported by policies that can increase production efficiency.